O papel do professor de ensino religioso no município de João Pessoa - PB - Lelis, Daniel Marcos Gomes de (2016)
This work is the result of dissertational study of the Religious Education teacher's role in the city of João Pessoa. In pursuit of this understanding, we have adopted the general objective; analyze the Religious Education teacher's role in municipal schools in João Pessoa, in the renewal of new knowledge and practice of teaching. The specific objectives were through the historical research in the construction of teacher identity of this curricular component and the identification of the components used in their educational practice that enables the student body the construction of critical thinking. The authors worked on the theoretical framework were Junqueira (2002), Silva (2011), Holmes (2010), among others. Thus, to obtain this understanding we use as methodology the qualitative approach, whose route was through exploratory and descriptive; as the technique used, we adopted the criteria of observation, semistructured interviews and data analysis. In this way, five (5) chapters were developed. In the first chapter, the motivations were presented, the objectives and the methodology of the work. In the second chapter, we discuss the historical process that legitimized the history of the presence of Religious Education in Brazil and in the city of João Pessoa. In the third chapter outline about being a teacher in the light of authors who significantly contributed to the educational activity in the Brazilian education scenario in religious education perspective. In the fourth chapter we had the concern to analyze the Religious Education teacher's role. Finally, in the fifth and final chapter, methodological procedures, followed by analysis of the data from which it was possible to obtain the desired results. Therefore, as a result we saw that the teacher's role in the municipal João Pessoa, corresponds to the objectives of PCNER and what is intended on Religious Education in the light of the main section 33 of Law 9.475/97.